1991
DOI: 10.1002/eji.1830210904
|View full text |Cite
|
Sign up to set email alerts
|

Antigen processing by endosomal proteases determines which sites of sperm‐whale myoglobin are eventually recognized by T cells

Abstract: This study reports an identification of the major processing products of an exogenous protein antigen, viz, sperm-whale myoglobin, as obtained after cell-free processing with partially purified macrophage endosomes. It is demonstrated that such a system yields fragments that are indistinguishable by high performance liquid chromatography analysis from those generated after uptake of myoglobin inside live macrophages. The concerted action of the endosomal proteases cathepsin D and cathepsin B can account for ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 53 publications
6
41
0
Order By: Relevance
“…The general structure of the FMDV dendrimeric peptide construction (B 4 T) used as the immunogen is depicted on Table 1. The construct is designed to display in a single molecule four copies of the VP1 (136 to 154) B-cell epitope (also known as antigenic site A) joined to a T-cell epitope from NS protein 3A (residues 21 to 35) through a lysine tree (54) plus two additional Lys residues defining a putative cleavage site for cathepsin D, a protease suggested to be involved during in vivo major histocompatibility complex (MHC) class II antigen processing (59). A convergent synthetic approach was chosen for B 4 T, based on the chemoselective thioether ligation (54) of (i) a tetravalent peptide reproducing the T-cell epitope, N-terminally elongated with two (cathepsin D site) plus three more Lys residues making up the dendrimeric core (these last three with their ␣ and ε amino groups functionalized as 2-chloroacetyl derivatives) ( Table 1); and (ii) a 19-residue peptide corresponding to the B-cell epitope, acetylated at the N terminus and C-terminally elongated with a Cys residue.…”
Section: Resultsmentioning
confidence: 99%
“…The general structure of the FMDV dendrimeric peptide construction (B 4 T) used as the immunogen is depicted on Table 1. The construct is designed to display in a single molecule four copies of the VP1 (136 to 154) B-cell epitope (also known as antigenic site A) joined to a T-cell epitope from NS protein 3A (residues 21 to 35) through a lysine tree (54) plus two additional Lys residues defining a putative cleavage site for cathepsin D, a protease suggested to be involved during in vivo major histocompatibility complex (MHC) class II antigen processing (59). A convergent synthetic approach was chosen for B 4 T, based on the chemoselective thioether ligation (54) of (i) a tetravalent peptide reproducing the T-cell epitope, N-terminally elongated with two (cathepsin D site) plus three more Lys residues making up the dendrimeric core (these last three with their ␣ and ε amino groups functionalized as 2-chloroacetyl derivatives) ( Table 1); and (ii) a 19-residue peptide corresponding to the B-cell epitope, acetylated at the N terminus and C-terminally elongated with a Cys residue.…”
Section: Resultsmentioning
confidence: 99%
“…This may be true, but we reasoned that lysosomal delivery of the epitope might nevertheless have been expected to result in MHC class II presentation and induction of CD4 ϩ T cells; therefore, the absence of a CD4 ϩ response to pCMV-GPTh-LII led us to hypothesize that the GP 61-80 epitope might be actively degraded in the lysosome. Cathepsin D, an endopeptidase which cleaves preferentially after hydrophobic residues (3), is the most abundant lysosomal enzyme involved in the generation of MHC class II peptides and has a profound effect on antigen processing (11,14,18,20,36,37,45,50). We investigated the effects of this enzyme on the GP 61-80 peptide and found that the peptide was cleaved after amino acid F 74 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro digestion of ovalbumin by the aspartyl protease cathepsin D, but not by the cysteine protease cathepsin B, generated peptides capable of stimulating T cells in association with class II molecules (114). Cathepsin D from bovine alveolar macrophages also produces epitopes capable of binding to class II molecules, which suggests a structural relationship between the antigenic motif generated by cathepsin D digestion and the antigenic structure recognized by MHC class II molecules (115). A specific inhibitor of the nonlysosomal aspartyl protease, cathepsin E, inhibited the processing of ovalbumin in a murine antigen-presenting cell line (116).…”
Section: Mhc Class II Antigen Presentation and Cathepsin Smentioning
confidence: 98%